INCENTIVO A PRODUÇÃO DE FLORES NA CIDADE DE BANANEIRAS – PB - Nascimento, Josias Pereira do; Moura, Fabiano Tavares de; Paixão, Adriano Soares da; Estrela, Francisco Abrantes; Martins, Laesio Pereira (Caderno Verde de Agroecologia e Desenvolvimento Sustentável, 2013)
_